How to improve program generasi berencana (GenRe) during the COVID-19 pandemic in DIY? - Nur Intan Kartika Sari (BKM Public Health and Community Medicine, 2021)
Objective: This paper aims to review Program Generasi Berencana (GenRe) and describe the effort to improve it during the COVID-19 Pandemic. Content: Indonesia is the 4th country with the largest population in the world. Sensus Penduduk 2020 recorded Indonesia's population in September 2020 as many as 270.20 million people where the majority of Indonesia's population is dominated by Generation Z (27.94%) and Millennial Generation (25.87%) of the total population in Indonesia. Program GenRe is the policy of the government for resolving the population problem also supporting Indonesian teenagers to be more visionary and useful for the nation. But its implementation experienced various challenges during the COVID-19 pandemic. The number of early marriages due to unwanted pregnancy in DIY had increased during the pandemic. Based on DIY Family Health Data records in 2017 there were 313 cases of unwanted pregnancies, then increased to 809 (2018) and rose to 938 cases (2019). Meanwhile, in 2020, it increased again to 1,009 cases of unwanted pregnancies in DIY, were in Yogyakarta as many as 125, Kulonprogo 131, Bantul 141, Gunungkidul 269, and Sleman 343. Some literature states that Game-Based Learning and Gamification can improve Sexual Health Education Programs to prevent unwanted pregnancy in adolescents. Besides, providing financial support (scholarship) and additional livelihood training and tutorial classes can keep adolescents in school and delay marriage. Of course, it is all also followed by the improvement of human resources managers, the development of Youth Family Development and Teenage/Student Counseling Information Center, improve socialization, and holding periodic program evaluations. Conclusion: There are many suggestions that were given to improve Program GenRe.